NECTROTIZING SOFT TISSUE INFECTION OF BREASTS: A STUDY OF CLINICAL PROFILE - KAPIL RAMPAL; HARKANWALPREET KAUR; JYOTI YADAV; SUDHIR KHICHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In this study, we aim to study the clinical profile of patients with necrotizing fasciitis of the breast and identify potential risk factors. Methods: It is a retrospective observational study. Case records, from January 2017 to December 2023, were observed for age, gender, occupation, socioeconomic status, body mass index (BMI) clinical features, and radiological findings (size, site, status, involvement of tissue compartments, and bone). A total of 22 patient records were evaluated. Results: We evaluated 22 patients and observed that all the patients were females, 54.5% of patients were in the 18–40 years age group. 59.1% of patients had BMI of more than 30 kg/m2. Pain and fever were the most common clinical presentations followed by local discharge. 90.9% of patients had leucocytosis and 81.8% were anemic. Raised bilirubin levels, raised international standardized ratio, and low albumin levels were found in more than 60% of cases. Diabetes mellitus was the most commonly associated co-morbidity seen in 63.6% of cases. We observed a total mortality of 18.1%. Conclusion: Necrotizing fasciitis of the breast is a rare disease. Outcomes may be poor in the form of extensive local mutilation, loss of breast tissue, and even mortality. An early and adequate management response is warranted.